Nexus Between Social Dimension and Financial Performance: a Bidirectional Study of the Nigerian Banking Industry - Dare John Olateju; Olakunle Abraham Olateju (Sekolah Tinggi Manajemen IPMI, 2023)
The study of CSR is gaining prominence because it is a critical component of business strategy that cannot be downsized due to its continued relevance to critical environmental, social, and governance impacts on our present world. The article mirrors the CSR implementation of Nigerian banks and its implication on their financial performance through the lens of legitimacy theory and vice versa. To know the financial indicator that determines the level of CSR performance. A panel data design was used to collect, arrange and analyse data. In other to regress the relationship between the social dimension of CSR and financial performance, we regress social dimension with PAT, EPS, and ROA using multivariate linear regression after taking into consideration all the relevant assumptions. The findings reveal that the social dimension has a positive relationship with PAT, EPS, and ROA. While social dimension shows a significant relationship between PAT and EPS but no significant relationship with ROA. PAT appeared to be a better predictor among the three financial predictors considered. To increase earnings, the findings suggest that firms can increase their social spending. As a single-case study, the findings may not be adequate for theoretical generalizations and therefore limited to the context of the study. This study adds to and expands the assumptions of legitimacy theory constructs by rethinking and exploring new assumptions in the context of the social dimension of CSR within the context of a developing country. It brings the theory to practice on strategic use of social dimension